Impatiens mukurthiana (Balsaminaceae) - A New species from the Nilgiri Biosphere Reserve, India - Tharani, Ravichandran; Murugesan, Maruthakutty; Ravichandran, Vellingiri; Anusuba, Veluswamy; Karthik, Bannari (Indian Forester, 2025)
No Abstract.